Visitors’ Emotions, Touristic or Spiritual Experiences in Historic Churches: The Development of Church Experience Scale (CES) - Mohd Kamal, Othman; Petrie, Helen; Power, Christopher (Elsevier Ltd., 2013)
In this paper we describe the development of the Church Experience Scale (CES) that allows us to measure visitor experience in historic churches, both with and without multimedia guides and other technologies. This study was carried out with 272 respondents at three historic churches in York, UK. Respondents for this study were visitors to these churches who were asked to complete a questionnaire immediately after their visit. A full psychometric scale development procedure was used which resulted in the Church Experience Scale (CES) which has five components: Enjoyment, Intellectual Stimulation and Curiosity; Emotional and Spiritual Experience; Immersion; Information Overload; and Knowledge and Learning. The usefulness of the scale in investigating visitors’ experiences in historic churches is explored. An initial comparison between inactive and an active historic church were compared using CES.